Simulação do efeito de retardo e aceleração de propagação de trincas para previsão de vida à fadiga de ligas de alumínio AA2050-T84 e 7475-T7351 de grau aeronáutico - Montezuma, Marcos Fábio Veríssimo (2022)
The study of life prediction and crack propagation in aeronautical grade aluminum alloys is of great importance in the development of projects in the aerospace industry. This work proposed the creation of an empirical numerical model, using concepts of fracture mechanics and fatigue, and based on experimental data produced in previous research, to evaluate the propagation of cracks in aluminum alloys 7475-T7351 and 2050-T84, considering the interaction effect and charge sequence. The model used the Paris-Erdogan and modified Walker equations and implemented a modification to the Wheeler crack tip plasticity-induced retardation model, to account for the effect of crack acceleration due to an underload. In the simulations for alloy 7475-T7351, constant-amplitude loading sequences were used, with increasing loading ratios R (0.1 / 0.3 / 0.5 / 0.6 / 0.7 / 0.8); for alloy 2050-T84, real sequences of standardized loadings, mini-TWIST and mini-FALSTAFF type were used. Finally, to evaluate the effect of crack retardation and acceleration, simulations were performed on alloy 2050-T84 considering constant amplitude loading, followed by peak overload; and peak overload + underload. The numerical results of constant amplitude were compared with the experimental results, other commercial programa, and the simulation through the finite element method. For alloy 7475-T7351, the simulation curves da/dN x K showed excellent agreement with the experimental curves. In simulations of 2050-T84 alloy with the mini-TWIST pattern, the crack growth curve correlated well with experimental data up to 150,000 life cycles. In simulations with the mini-FALSTAFF pattern, the crack growth curve had a good correlation with experimental data up to 27000 life cycles. In all the simulations performed, the use of the modified Walker equation with a variation of the parameter R, together with the modified Wheeler model, obtained the best results compared to the use of the Paris-Erdogan equation without the effect of load interaction. It was verified that the application of overloads every 1000 cycles in constant amplitude loading, caused the extension of the life of the CP 6 times, being beneficial for the fatigue life of the component. On the other hand, the application of the underload acted as a reducer of fatigue life. It is expected that the developed model can contribute to the construction of an open-source platform, related to the fatigue phenomenon, to provide independent analyzes of closed programs that are generally paid and without the possibility of expanding their functionalities by part of the user. This methodology can be used in several areas and the aeronautical industry, where improvement in the development of new design criteria is necessary. Neglecting the effects of the interaction of loads makes the life prediction analysis very conservative, not being suitable for use in current projects.